EFFECT OF DEPLETION PERCENTAGE ON YIELD , YIELD COMPONENTS AND WATER USE EFICIENCY FOR SELECTED GENOTYPES OF BREAD WHEAT - & Dhahi, Baktash (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2018)
A field experiments were carried out at the Abu- Graib Research Station - Office of Agricultural Research Ministry of Agriculture , to investigate effect of moisture deletion for some traits of selected wheat genotypes , during 2014-2015, which depend to the long term of breeding program (2008-2014) . The 9th selected genotypes and the control variety IPA 99 were evaluated using split plot arrangement within RCBD and three replications. The main plots included four moisture depletion (20%, 40%, 60% and 80%) of available water while, genotypes occupied sub plots .The results revealed significant differences among depletion, genotypes and their interaction of all studied traits. Moisture depletion 20% , showed the superiority of number of spikes m-2 (385.7), number of grains spike-1 (57.23 grain), weight of 1000 grains (40.85 gm), higher grain yield (5.06 t ha-1), higher biological yield (16.51 t ha-1), and highest water use efficiency for grain yield (1.63 kg m-3). Significant differences were found among genotypes and interactions between genotypes and water stress in most studied characters , this shows of genotypes performance differences to water stress. So we can select one or more genotype which tolerance to water stress.